The 3'-untranslated region contributes to the pregnane X receptor (PXR) expression down-regulation by PXR ligands and up-regulation by glucocorticoids - Smutny, Tomas; Dusek, Jan; Hyrsova, Lucie; Nekvindova, Jana; Horvatova, Alzbeta; Micuda, Stanislav; Gerbal-Chaloin, Sabine; Pavek, Petr (Acta pharmaceutica Sinica. B, 2020)
Pregnane X receptor (PXR) is the major regulator of xenobiotic metabolism. PXR itself is controlled by various signaling molecules including glucocorticoids. Moreover, negative feed-back regulation has been proposed at the transcriptional level. We examined the involvement of the 3'-untranslated region (3'-UTR) of NR1I2 mRNA and microRNAs in PXR- and glucocorticoid receptor (GR)-mediated regulation of NR1I2 gene expression. PXR ligands were found to significantly downregulate NR1I2 mRNA expression in a set of 14 human hepatocyte cultures. Similarly, PXR was downregulated by PCN in the C57/BL6 mice liver. In mechanistic studies with the full-length 3'-UTR cloned into luciferase reporter or expression vectors, we showed that the 3'-UTR reduces PXR expression. From the miRNAs tested, miR-18a-5p inhibited both NR1I2 expression and CYP3A4 gene induction. Importantly, we observed significant upregulation of miR-18a-5p expression 6 h after treatment with the PXR ligand rifampicin, which indicates a putative mechanism underlying NR1I2 negative feed-back regulation in hepatic cells. Additionally, glucocorticoids upregulated NR1I2 expression not only through the promoter region but also via 3'-UTR regulation, which likely involves downregulation of miR-18a-5p. We conclude that miR-18a-5p is involved in the down-regulation of NR1I2 expression by its ligands and in the upregulation of NR1I2 mRNA expression by glucocorticoids in hepatic cells.
Keywords: DEX, dexamethasone; CAR, constitutive androstane receptor; Gene expression; ER, estrogen receptor; Pregnane X receptor; LBD, ligand binding domain; PB, phenobarbital; 3′-UTR, 3′-untranslated region; PCN, pregnenolone 16α-carbonitrile; GRα, glucocorticoid receptor α; PXR, pregnane X receptor; RXRα, retinoid X receptor α; PPARα, peroxisome proliferator-activated receptor α; Cytochrome P450 3A4; SEAP, secreted alkaline phosphatase; DMSO, dimethyl sulfoxide; MicroRNA; NR, nuclear receptor; CYP3A4, cytochrome P450 3A4; Rif, rifampicin; DMEs, drug metabolizing enzymes; Glucocorticoid; Regulation; PHHs, primary human hepatocytes; Gluc, Gaussia luciferase; miRNA, microRNA; MRE, miRNA-response element